Weight reduction and strengthening of marine hatch covers by using composite materials - Tawfik, Basem E.; Leheta, Heba; Elhewy, Ahmed; Elsayed, Tarek (International journal of naval architecture and ocean engineering, 2017)
The application of composites as an alternative material for marine steel hatch covers is the subject of this study. Two separate approaches are considered; weight reduction approach and strengthening approach. For both approaches Finite Element Analysis (FEA) was performed using ANSYS software. Critical design parameters of the composite hatch cover and FEA are discussed in details. Regarding the weight reduction approach; steel hatch covers of a bulk carrier were replaced by composite covers and a weight reduction of 44.32% was achieved leading to many benefits including fuel saving, Deadweight Increment and lower center of gravity of the vessel. For the strengthening approach; the foremost hatch cover was strengthened to withstand 150% of the load required by IACS for safer navigation while no change in weight was made between the steel and composite covers. Results show that both approaches are feasible and advantageous.